2016
DOI: 10.1002/j.1681-4835.2016.tb00519.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Mobile Phones In The Development Of Social Capital Among Refugees In South Africa

Abstract: Mobile phones have been identified as possible tools to aid in refugee integration into new countries. Using a social capital theoretical lens, the role of mobile phones in the development of social capital among refugees in South Africa is explored. Semi‐structured interviews were conducted with 29 refugees in South Africa. Findings indicate that mobile phones can play an important role in the development of bridging social capital thereby aiding in the social and economic integration of refugees into the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
1
23
1
1
Order By: Relevance
“…The ethnographic study with 29 refugees living in South Africa by Bacishoga, Hooper, and Johnston et al [48] reported that MPs played an important role in the development of bringing social capital, thus supporting social and economic integration of refugees into the new community. Indeed, MPs favored weak links with people with whom refugees studied, worked, and shared accommodations or similar interests, also aiding refugees to get involved in different group activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethnographic study with 29 refugees living in South Africa by Bacishoga, Hooper, and Johnston et al [48] reported that MPs played an important role in the development of bringing social capital, thus supporting social and economic integration of refugees into the new community. Indeed, MPs favored weak links with people with whom refugees studied, worked, and shared accommodations or similar interests, also aiding refugees to get involved in different group activities.…”
Section: Resultsmentioning
confidence: 99%
“…Also in their study the digital divide–related to the migrants’ digital skills and to the ability to pay for the services–was a critical aspect of refugees’ social inclusion in the broader Australian community. Similarly, cost, connectivity, and perceived usefulness, influenced MPs use in the 29 South Africa refugees that participated in the ethnographic study by Bacishoga, Hooper, and Johnston [48].…”
Section: Resultsmentioning
confidence: 99%
“…Alam and Imran's (2015) study, for instance, revealed that issues related to income, mobility, and availability greatly constrained ICT usage among different refugee migrant groups in Australia, especially for the newly arrived who experienced major barriers to internet access and use due to affordability, language, and literacy issues. Similarly, Bacishoga, Hooper, and Johnston (2016) showed that cost, access, and perceived utility of mobile phones by refugees in South Africa shaped their adoption of these technologies.…”
Section: The Role Of Mobile Phones For Refugee Resettlementmentioning
confidence: 99%
“…In line with Zinnbauer (2007), Dekker and Engbersen (2014) found out that ICT promoted the creation of new bridging networks resourceful for migrants’ establishment in the reception community. Additionally, Bacishoga et al (2016) argue that technologies allow migrants to strengthen the bridging networks that they had already created through physical encounters.…”
Section: Theoretical Backgroundmentioning
confidence: 99%